Black Wattle Mortality - Preliminary Studies on Black Wattle Acacia mearnsii (A. Mollissima) Soils from Nilgiris - Chayanuiu, M. V.; Balakrishnan, K. S. (Indian Forester, 1980)
Black wattle (A mearnsii), one of the tan bark wattles is raised in Nilgiris and Kodaikanal in Tamil Nadu. Mortality in black wattle was reported from the Nilgiris and this work was taken up to ascertain whether any soil factor may be responsible for this. Soil samples were collected from different localities in the Nilgiris covering various age groups of the plantations, and physical and chemical characteristics were determined. Comparison of the analytical data of soil samples within the profile and between the profiles does not show any significant difference, and the depth of soil also does not bear any relation to the mortality, as shallow soils bear good growth, compared to high and moderate mortality on deep, medium textured soils. It can be concluded that the soil factors analysed for do not bear any relation to the black wattle mortality. A study of the aspect, the percentage of slope and the speed and the direction of wind may help in finding out the reason for this mortality in the black wattles.